2010
DOI: 10.1016/j.bpj.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An Oligomeric Equilibrium Intermediate as the Precursory Nucleus of Globular and Fibrillar Supramacromolecular Assemblies in a PDZ Domain

Abstract: The equilibrium unfolding at neutral pH of the third PDZ domain of PSD95, as followed by DSC, is characterized by the presence of an equilibrium intermediate with clear signs of oligomerization. DLS and SEC measurements indicate that at 60-70 degrees C small oligomers populate, showing a typical beta-sheet far-UV CD spectrum. These intermediate species lead to the formation of rodlike particulates of approximately 12 nm, which remain in solution after 2 weeks incubation and grow until they adopt annular/spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(94 citation statements)
references
References 37 publications
17
77
0
Order By: Relevance
“…As we showed in a previous work [4], the thermal unfolding of PDZ3 at neutral pH reveals the presence of an oligomeric equilibrium intermediate that populates maximally at around 60-70 ºC. The DSC traces comprise two well separated unfolding transitions, which can be fully described by a three-state association-dissociation equilibrium model (nN ⇄ I n ⇄ nU).…”
Section: Pdz3 Unfolds Under An Apparent Two-state Scheme At Acidic Phsupporting
confidence: 57%
See 3 more Smart Citations
“…As we showed in a previous work [4], the thermal unfolding of PDZ3 at neutral pH reveals the presence of an oligomeric equilibrium intermediate that populates maximally at around 60-70 ºC. The DSC traces comprise two well separated unfolding transitions, which can be fully described by a three-state association-dissociation equilibrium model (nN ⇄ I n ⇄ nU).…”
Section: Pdz3 Unfolds Under An Apparent Two-state Scheme At Acidic Phsupporting
confidence: 57%
“…PDZ3 experimental conditions were 50 mM buffer (either phosphate at pH 7.5, acetate at pH 4.0 or glycine/HCl at pH 2.0-3.5). DLS, CD and ThT and ANS fluorescence experimental details can be obtained from previous references [4,11]. TEM images of amyloid fibrils were made at the CIC services of the University of Granada.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamic data on the stability of amyloid fibrils obtained by DSC (Morel et al 2010) and ITC (Kardos et al 2004) indicate the contribution of entropy increase attained with their assembly, which points toward hydration effects playing a major role in this process. Previous DSC studies have also shown that thermalinduced aggregation of several proteins is accompanied by the exothermic effect of heat (Dzwolak et al 2003;Stirpe et al 2008;Attanasio et al 2009;Murciano-Calles et al 2010). Such an effect may be explained by a nucleation model, i.e., the formation of a stable nucleus that incorporates additional monomeric proteins into a growing aggregate (Dzwolak et al 2003), but the exact molecular basis remains elusive.…”
Section: Introductionmentioning
confidence: 99%